Czynniki determinujące konkurencyjność wybranego gospodarstwa agroturystycznego - Lesiów, Tomasz; Zeler, Beata (Factors Affecting Competition of the Selected Agritourism Farm, 2006)
The aim of the paper is to present a number of conditioning which have influence on the proper functioning and success in agritourism farm. To be the most successful in their operations in agricultural tourism farmers have to share a set of important qualifications: an outgoing personality that enjoys interacting with the public, a property that is attractive and organized, a product (activity based, object, or service) that people desire, marketing ability, the knowledge of law regulations concerning ecology, food safety and people security. Important is also cooperation with a local community in the process of new investments and improving the quality of offered services as well as with other farmers in the area of advertisement and promotion.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 28-33